Adoption of Social Media for Health Education Among Female Residents of Karu Local Government Area - Bako, Tulo James (Lembaga Yasin AlSys, 2025)
Social media is use for health interventions. This study was conducted to investigate the adoption of social media for health education among female residents of Karu Local Government Area. The study was underpinned on the unified theory of acceptance and use of technology supported by the social identity theory (SIT) and social shaping of technology theory. The study employed a survey research design, utilizing a combination of questionnaires and in-depth interviews as data collection tools. A sample size of 384 participants was carefully selected from the target population. Results from the study revealed that female residents of Karu local government adopt social media for health education. Further findings revealed that female residents of Karu to a large extent access and use health education on social media. It was also found that health education accessed by female residents of Karu on social media was beneficial to them and their network of friends and relatives while the health topics frequently accessed are maternal health, female hygiene and early child care. The study conclude that health education accessed on social media platforms Facebook, YouTube, X and other sites like Google and Medical websites can be beneficial for improvement of wellbeing, information sharing, and professional development. Promoting health issues awareness, receiving updates, staying in contact with healthcare professionals, and using it for research are other advantages. The study suggests prioritizing the establishment of healthcare facilities in rural areas to minimize the distance between rural populations and accessible healthcare services.